Exploring the factors influencing high school students' deep learning of English in blended learning environments - Shi, Hong; Lan, Peng (Frontiers in Education, 2024)
This study examines influencing factors (i.e. self-efficacy, learning engagement, and teacher-student interaction) of high school students' English deep learning in blending courses. Research hypotheses are proposed, and a structural equation model (SEM) of influencing factors of deep learning is built. A sample size of 225 participants was recruited on a voluntary and anonymous basis from a high school in Southwestern China for this study.We find: 1) self-efficacy, learning engagement and teacher-student interaction all predict and have positive impacts on English deep learning; 2) self-efficacy has a positive impact on learning engagement and teacher-student interaction; 3) teacher-student interaction has a positive impact on learning engagement. The findings underscore the importance of self-efficacy, learning engagement, and teacher-student interaction for EFL high school learners to achieve deep learning in a blending context. Drawn from these findings, pedagogical implications for promoting these learners' deep learning are provided.